The Influence of Tourism Attraction Levy Receipts on Original Regional Income in Ngada Regency - Klementiana Fao Gholo; Nikson Tameno; Cicilia A. Tungga (PT FORMOSA CENDEKIA GLOBAL, 2023)
This exploration was directed determined to figure out the impact of vacation spot demand receipts on the nearby pay of Ngada Rule from 2016-2021. The information utilized in this examination is optional information. Perception, documentation and interview information assortment strategies were then investigated utilizing a basic direct relapse examination strategy utilizing the SPSS application. The consequences of this examination show that the receipt of vacation spot demands fundamentally affects nearby unique pay. This depends on the t test worth of the duty receipt variable of 3.297 and a critical worth of 0.030 which is more modest than the foreordained huge worth of 0.05 (5%